Variability and Scope of Improvement in Lasora (Cordia myxa) - Samadia, D.K. (Indian Journal of Agroforestry, 2020)
A rich reserve of genetic variability in hardy fruit species such as khejri, lasora, jharber, bordi, ker, pilu, etc. in the traditional arid farming system has sustained substantial nutritional needs and livelihood of the desert dwellers. Lasora is an importantfruit species and is considered as a herbal tree in rural India. Two explorations were made during 2000 and 2001 for the surveys and collections of lasora variability in the state of Rajasthan. The germplasm was collected from 95 sites with varied agro-climatic conditions. A wide range of variations was observed for the important characters on plant growth, leaf size, fruit size, and fruit quality and yield components. The analysis of variance revealed that there were high and significant differences among the thirty groups of lasora population. The estimation of GCV and PCV for fruit weight and leaf size was high and therefore, good scope for improvement through selection. High estimate of heritability along with high genetic advance as per cent of mean was estimated for fruit weight (79.95), leaf size (89.72) and leaf width (53.73). Positive and highly significant correlations were observed between fruit weight and fruit length and diameter. On the basis of correlation studies, it could be suggested that plants with large sized leaves would give bigger sized fruits and viceÂ versa.